Cork oak transplant: A new reality? A Physiological Approach to maximize sucess rate. - Dinis, C (2016)
Cork oak tree (Quercus suber L.), in Portugal, is considered the national tree and have special demands and legal protection when dealing with silviculture management (pruning, debarking, thinning). Being a species of slow growth, cork oak transplanting procedures can be a valuable asset either from the economic or ecological rationales to relocate trees, re-populate areas affected by high tree mortality, increase tree density to control erosion on montado ecosystems or landscape design. This study focuses the impacts and physiological responses of ten juvenile rain fed cork oak trees (with diameter at breast height between 6 and 16cm), when subjected to transplant operations. The work was conducted in a cork oak woodland experimental plot at the campus of the University of Évora (SW Portugal), during the year of 2015. Tree’s transplants were performed with a truck-mounted hydraulic spade transplanter coupled with a proposed methodology to maximize tree survival rates, addressing techniques to limit canopy transpiration and to improve root systems prior to transplant. Tree ecophysiological indicators (sap flow, leaf water potentials and stomatal conductance) were monitored comprising the periods before and after transplant operations, and water stress avoidance practices were established to promote post-transplant tree status recovery, including irrigation to match average daily accumulated sap flow. Transplant operations were considered successful when the tree's water uptake inferred from sap flow exhibited a high correlation with solar radiation and returned to its undisturbed or pre-transplant water potential gradients in the following 2 to 3 weeks. The post-transplant tree nourishment follow up included permanent sap flow measurements and identified the time elapsed after transplantation from which the tree recovers its normal transpiration thresholds and response. Our results suggest that by following the proposed methodology the sampled cork oak trees exhibited a transplant success rate of 90%.